2010
DOI: 10.1186/1743-7075-7-34
|View full text |Cite
|
Sign up to set email alerts
|

Association of macrophage inhibitory cytokine-1 with nutritional status, body composition and bone mineral density in patients with anorexia nervosa: the influence of partial realimentation

Abstract: BackgroundMacrophage inhibitory cytokine-1 (MIC-1) is a key inducer of cancer-related anorexia and weight loss. However, its possible role in the etiopathogenesis of nutritional disorders of other etiology such as anorexia nervosa (AN) is currently unknown.MethodsWe measured fasting serum concentrations of MIC-1 in patients with AN before and after 2-month nutritional treatment and explored its relationship with nutritional status, metabolic and biochemical parameters. Sixteen previously untreated women with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
1
23
1
2
Order By: Relevance
“…We reported higher fasting serum MIC‐1 levels in patients with AN in comparison with obese subjects and normal‐weight controls. Increased levels of MIC‐1 in AN were also observed in one recent study 11 . In our study, there were no differences in fasting MIC‐1 concentrations between obese women and controls.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We reported higher fasting serum MIC‐1 levels in patients with AN in comparison with obese subjects and normal‐weight controls. Increased levels of MIC‐1 in AN were also observed in one recent study 11 . In our study, there were no differences in fasting MIC‐1 concentrations between obese women and controls.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, both baseline and postclamp MIC‐1 were inversely related to the body weight and BMI. Other investigators also found significant negative correlation between MIC‐1 concentration and BMI 11 . Additionally, elevated serum MIC‐1 concentrations in patients with AN were significantly reduced by partial realimentation, but it still remained significantly higher compared with controls 11 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, these results suggest an indirect association between GDF-15 and insulin resistance, and the pathophysiological mechanisms that control postoperative GDF-15 concentrations remain unknown. It is interesting to note that GDF-15 concentrations also increase after diet-induced weight loss and in patients with anorexia nervosa (13,25 ). To date, it is not known whether circulating GDF-15 concentrations depend on albumin or any carrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This is also reflected in measurements of single antioxidant markers such as albumin, apolipoprotein B, and uric acid [23,[25][26][27][28]. Diminished uric acid level was also observed in extended period of time after realimentation [29].…”
Section: Discussionmentioning
confidence: 99%